THE EFFECTIVENESS OF ANTENATAL HYPNOTHERAPY ON ANXIETY IN FACING THE CHILDBIRTH PROCESS - Octavia, Yunida Turisna; Hasibuan, Eva Kartika; Siahaan, Julia Mahdalena (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
The Maternal Mortality Rate (MMR) in Indonesia is still around 305 per 100,000 Live Births, which has not yet reached the set target of 183 per 100,000 LB in 2024. One of the causes of this high rate is attributed to the anxiety experienced during pregnancy, reaching 373,000 cases. Antenatal hypnotherapy is an effort aimed at reducing maternal anxiety with the goal of preparing for a normal pregnancy and facilitating the labor process. Hypnotherapy in Antenatal care focuses on providing comfort to mothers by inducing deep relaxation. The purpose of this study is to determine the effectiveness of antenatal hypnotherapy in reducing anxiety during the labor process at PMB Pera Medan. The research employed a quantitative approach with a Quasi-Experimental Design (pseudo-experiment). The study utilized a One Group Pre-Test and Post-Test design. The population consisted of all third-trimester pregnant women at PMB Pera Medan, totaling 61 pregnant women, with a sample size of 16 selected through purposive sampling. The research findings indicate that the average anxiety level among third-trimester pregnant women at the Independent Practice of Midwife Pera Medan before receiving antenatal hypnotherapy was 30.1875 (moderate anxiety), which decreased to 13.8750 (mild anxiety) after receiving antenatal hypnotherapy. There is a significant influence of antenatal hypnotherapy on reducing anxiety during labor at PMB Pera Medan with a p-value of 0.000 < 0.05. Therefore, it is advisable to continue antenatal hypnotherapy classes for pregnant women during each ANC visit and at home to reduce anxiety, thereby facilitating a normal labor process.